Respostas biomecânica e sensorial dos músculos posteriores da coxa submetidos à vibração mecânica localizada e ao treinamento da flexibilidade com sobreposição da vibração mecânica localizada - Beatriz Magalhaes Pereira (2016)
Mechanical vibration has been used to potentiate joint range of motion (ROM) gain, however, there is no consensus on how controls and measures of vibration stimulus parameters or data related to their effect on biomechanical and sensory muscles variables. The purposes were to compare the acute effect of the manipulation of the parameters of the localized vibration stimulus and the chronic effect of flexibility training combined with different parameters of the localized vibration stimulus on maximum ROM (ROMMÁX), maximum torque (TORQUEMÁX), subjective perception of stretching discomfort (values of ROM, ROMFST), torque, TORQUEFST, corresponding to the moment when the individual registers a first sensation of tension at the hamstrings) and passive stiffness. Two experiments were performed (E1 and E2) in which ROMMÁX, TORQUEMÁX, ROMFST and TORQUEFST were measured by the equipment Flexmachine, and passive stiffness calculated later. In E1, 10 men underwent different localized vibration conditions at hamstrings (NV no vibration, V1 frequency=14Hz/amplitude=3mm, V2 14Hz/6mm, V3 24Hz/3mm, V4 24Hz/6mm). ). In the conditions V1, V2, 3 and V4 the average gain of ROMMAX and ROMFST was increased with no difference between the conditions. Experiment 2 was composed by 46 men, random into 4 groups: CON (n = 10), control; SS (n = 12), who underwent passive-static stretching for 4 weeks (4x30s, 3x/week, 90% of the pre-test ROMMÁX), GV1 (n = 12) and GV2 (n = 12) who underwent to the same training of SS with localized mechanical vibration overlap (amplitude=3mm and frequency of 14Hz and 24Hz, respectively). There was a marked increase in the average gain of ROMMAX, TORQUEMAX, ROMFST and TORQUEFST, for in SS, GV1 and GV2 groups compared to CON with no difference between groups.